The Secret of Brotherhood-Based Education: A Holistic Ice-Breaking Strategy for Islamic Schools - Nurdalia, Nurdalia (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Islamic education often faces challenges in realizing solid Islamic brotherhood, where students tend to be rigid, less interactive, and compartmentalized, hindering character formation and collaboration. This study intends to analyze and formulate a holistic and sharia-relevant icebreaking optimization model as a primary strategy for strengthening brotherhood in Islamic schools. The method used is descriptive qualitative, with a case study approach in the Islamic School in Wajo Regency, involving participatory observation and in-depth interviews with teachers and students. The results indicate that the implementation of the 3-S Strategy (Salam, Senyum, Sapa) through structured icebreaking, integrated with the values of adab and muamalah, is proven effective in increasing self-disclosure and empathy among students. The main contribution of this finding is the hidden curriculum model that positions icebreaking not just as a break, but as an essential component of character education. This model provides practical contributions for Islamic educators and institutions to create a warm, inclusive, and strong learning ecosystem based on brotherhood.